Can the PRISMA Protocol be used to Guide a Systematic Literature Review of Antecedents of Policy Innovation Trailblazing and Adoption? – I - Glor, Eleanor D (Innovation Journal, 2021)
Methodology for systematic literature reviews (SLRs) is not well developed in public policy compared to the health field. This paper explores use of the health PRISMA protocol for SLRs to guide an SLR of antecedents of trailblazing and adoption of public policy innovation and whether it is a suitable protocol for public policy. Trailblazing is the first two stages—invention and early adoption—of Rogers’ (1995) five stages of innovation adoption in a governmental or organizational population. Completing applicable items in the checklist, a SLR of 87 peerreviewed publications identified 594 antecedents; trailblazing/adoption and empirical/nonempirical studies are distinguished and the theories reflected are identified.
Number: 2